Preparation and Characterization of Composite Cellulose Acetate/NaA Zeolite/Alumina Membrane and Its Application in Vetiver Oil’s Pervaporation - Asep Hadian Hadinata; Engela Evy Ernawati; Agnes Rezky Siahaan (Jurnal Kimia Valensi, 2019)
Rice husk is an agricultural waste that contains cellulose. Risce husk’s cellulose can be converted to cellulose acetate. Cellulose acetate (CA) is widely used as membrane’s material for pervaporation. This material has high swelling degree that can influence its performance. The membrane’s performance can be improved by addition of minerals such zeolite and alumina. The purpose of this study was to determine the characteristics and the best composition of CA/NaA zeolite/alumina composite membrane (CA/Na/Al) for pervaporation of Vetiver oil. Methods that has been done were acetylation of rice husk’s cellulose, synthesis of composite membrane, characterization, and pervaporation of Vetiver oil. Focused characteristics of membrane were its swelling degree, mechanical strength, and its morphology. Composite CA/Na/Al membrane has lower swelling degree than CA/NaA membrane because the existence of alumina that fill CA matrix. The optimum mechanical strength was gained by adding 2% alumina to membrane. But, composite CA/Na/Al 3% membrane was the best composition due to its performance. Membrane performance including its flux and the percentage of vetiverol gained (Cp), with flux value 367.83 g.m-2.h-1 and Cp value 15.584%.